Impact of the Naples Prognostic Score at admission on long-term prognosis among patients with coronary artery disease - Wang, Bo; Chen, Wan; Shi, Lei; Pei, Mingyu; Zhou, Yao; Wei, Yanlin; Tang, Yutao; Qiu, Guozheng; Duan, Wenlong; Chen, Shengxin; Chen, Xiangrong; Zhang, Zhongyuan; et al. (Frontiers in Immunology, 2025)
BackgroundThe Naples Prognostic Score (NPS) is innovatively constructed to comprehensively evaluate the inflammatory and nutritional status according to several basic blood examinations. This study aimed to investigate the correlation between NPS and long-term prognosis in patients with coronary artery disease (CAD).MethodsThe analysis data of this retrospective cohort study were collected from electronic health records in the People’s Hospital of Guangxi Zhuang Autonomous Region. All adult patients who underwent coronary angiology (CAG) and were diagnosed as having CAD at the People’s Hospital of Guangxi Zhuang Autonomous Region from March 2013 to December 2023 were enrolled. The primary endpoint was all-cause death during follow-up.ResultsThe 28,799 patients were divided into three groups according to the NPS value, with 803 (2.79%) in group 0, 12,130 (42.12%) in group 1, and 15,866 (55.09%) in group 2. Over the median follow-up period of 6.12 years, 3,630 patients (12.60%) died. Long-term all-cause mortality was significantly higher in group 2 and group 1 compared with group 0 (log-rank p < 0.001). Cox regression analysis showed that both continuous NPS and categorical NPS groups were significantly associated with the risk of all-cause mortality in patients with CAD [per 1-point decrement: full adjusted HR = 1.15; 95% CI, 1.11–1.19; compared with group 0 (NPS of 0), group 1 (NPS of 1 or 2), full adjusted HR = 1.38, 95% CI: 1.03–1.85, and group 2 (NPS of 3 or 4), full adjusted HR = 1.70, 95% CI: 1.27–2.28]. Restricted cubic spline analyses showed a linear relationship between NPS and risk of long-term all-cause death.ConclusionsThe present study demonstrates that the NPS was independently associated with long-term all-cause mortality among patients with CAD.